Chalcogen Bonding in Protein-Ligand Complexes: PDB Survey and Quantum Mechanical Calculations - Kříž, Kristian; Fanfrlík, Jindřich; Lepšík, Martin (Chemphyschem, 2018)
A chalcogen bond is a nonclassical noncovalent interaction which can stabilise small-molecule crystals as well as protein structures. Here, we systematically explore the stabilising potential of chalcogen bonding in protein-ligand complexes in the Protein Data Bank (PDB). We have found that a large fraction (23 %) of complexes with a S/Se-containing ligand feature close S/Se⋅⋅⋅O/N/S contacts. Eleven non-redundant representative potential S/Se⋅⋅⋅O chalcogen-bond motifs were selected and truncated to model systems and seven more model systems were prepared by S-to-Se substitution. These systems were then subjected to analysis by quantum chemical (QM) methods-electrostatic potential, geometry optimisation or interaction energy calculations, including solvent effects. The QM calculations indicate that chalcogen bonding does indeed play a dominant role in stabilising some of the interaction motifs studied. We thus advocate further exploration of chalcogen bonding with the aim of potential future use in structure-based drug design.
Keywords: σ-hole; noncovalent interactions; quantum chemistry; drug design; Protein Data Bank